Economic values associated with expected progeny differences (EPD) for angus bulls at auction - Dhuyvetter, Kevin C.; Jones, R.; Turner, T.; Marsh, T. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The two primary objectives of this study were to re-examine the economic values of production expected progeny differences (EPD) and how they relate to the values assigned to actual weights, and to assess the impact that ultrasound EPD have on Angus bull prices. Buyers consider the EPD birth weight to be more important than actual birth weight when selecting bulls. For the remaining production EPD, however, the actual measures were considered more important than the EPD. All four ultrasound EPD were significantly related to price, with three out of the four exhibiting the expected response. Comparisons among premiums/discounts associated with ultrasound EPD, production EPD, and actual weights showed that EPD for ultrasound ribeye area had significantly larger price responses than did either the EPD for birth weight or the actual adjusted yearling weight. This finding suggests that breeders who currently fail to report this data should consider its inclusion in future production sales.
Keywords: Beef; EPD's; Angus bulls